2016
DOI: 10.1590/0102-311x00066215
|View full text |Cite
|
Sign up to set email alerts
|

Eating patterns in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil): an exploratory analysis

Abstract: The food consumption of 15,071 public employees was analyzed in six Brazilian cities participating in the baseline for Brazilian Longitudinal Study of Adult Health (ELSA-Brasil, 2008-2010) with the aim of identifying eating patterns and their relationship to socio-demographic variables. Multiple correspondence and cluster analysis were applied. Four patterns were identified, with their respective frequencies: "traditional" (48%); "fruits and vegetables" (25%); "pastry shop" (24%); and "diet/light" (5%) The "tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 44 publications
9
39
1
12
Order By: Relevance
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…28,30,33 However, because a low-protein diet is recommended for non-dialysis CKD patients, we consider that high intake of meats, and consequently protein, may not be healthy or prudent in this population, and thus we name this pattern "mixed. " The traditional pattern was directly associated with male gender and inversely associated with age, as found by Cardoso et al 34 in a population study. Male gender was also associated with the snack pattern, as verified by Ferreira et al, 32 which may indicate a minor concern regarding feeding among men.…”
Section: Discussionsupporting
confidence: 64%
“…However, this is mi-tigated by detailing all the decisions taken 30 . Similarly, despite the explained variance of dietary patterns standing at around 20%, other studies in the area use values close to this variation 29,31 and others do not question this situation 30,33,36 . Moreover, the detected dietary patterns were comparable with other studies, characterizing their external validity 24,[29][30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 75%
“…In addition, intake of typical foods by bank employees did not saturate in the pattern of "vegetables, fruits, cereals and tubers", a fact that is in line with the current diet of the Brazilian population, characterized by low intake of fruits and vegetables, despite maintained consumption of rice and beans by a large part of the population. When analyzing the compliance of bank employees' dietary patterns with the other researches that applied the methodology of ACP for the study of food consumption, similarities were identified in their results, since the appearance of groups with traditional foods, foods recognized as healthier snacks 24,[29][30][31][32][33][34][35][36] . Teachers from the city of Tehran (Iranian capital) 31 , employees of a Japanese factory and 33 , recently, Brazilian civil servants had the food consumption assessed by the ACP 36 , showing that there are few publications about food consumption of groups of workers in the form of dietary pattern.…”
Section: Discussionmentioning
confidence: 99%